Conjugation of an anti-metabolite nucleobase analogue with a mitochondriotropic agent via palladium(II) against breast cancer cells - Banti, C. N.; Tasiopoulos, A. J.; Hadjikakou, S. K. (Frontiers in Chemical Biology, 2024)
The conjugation of the uracil (a nucleobase) analogue, 6-methyl-thiouracil (MTUC), with the mitochondriotropic agent of Tri-o-Tolyl-Phosphine (TOTP) though palladium(II) leads to the formation of the metallodrug of formula [PdCl(TOTP)(MTUC)] (1). The metallodrug was characterized in solid state using Attenuated Total Reflectance-Fourier Transform Infra-Red (ATR-FTIR) spectroscopy and X-ray diffraction crystallography (XRD), while its behavior in solution was examined through Ultra Violet (UV) and 1 H NMR spectroscopies. The in vitro cytotoxicity of 1 was assessed against human breast adenocarcinoma cell lines: MCF-7 (hormone-dependent (HD)) and MDA-MB-231 (hormone-independent (HI)), as well as fetal lung fibroblast (MRC-5) cells. The MCF-7 cells morphology suggests apoptotic pathway, and this was confirmed by Acridine Orange/Ethidium Bromide (AO/EB) Staining, and the loss of the permeabilization of the mitochondrial membrane. The binding affinity of 1 toward the calf thymus (CT) DNA was clarified.